(untitled) (Discourse of Law and Administration, 2021)
The article addresses the issues of Chapter 7a of the Energy Law which are criminal law regulations that were introduced to the Polish legal order in connection with EU Regulation 1227/2011 (REMIT) in 2015. With this regulation, European authorities ordered Member States to introduce sanctions into their national order for behavior that is prejudicial to the transparency of wholesale energy markets. The Polish legislator has restricted some of these behaviors with administrative sanctions, and some with criminal sanctions. The purpose of the article is to verify the correctness of the solutions adopted by the Polish legislator in the field of criminal provisions introduced into the energy law in connection with the presented regulation. The authors will analyze from the perspective of both the basic assumptions and functions of criminal law, and the principles of correct legislation. They will also indicate that the use of criminal law instruments under current energy law regulations is not entirely adequate, and sufficient to achieve the purpose of the REMIT regulation is to reach for solutions appropriate to administrative law.